Melody and meaning: the semiotics of ancient Greek music in the late classical and early Hellenistic eras - Klavan, S (2019)
Melody and Meaning asks what music can communicate, and how, according to critics and philosophers from the late Classical and early Hellenistic periods. What can melody express, if anything, and how does it exert its powerful emotional force on those who listen to it? These are among the most enduring and difficult questions in aesthetics – they have been subjects of lively debate among modern scholars such as (to name just a few) Eduard Hanslick, Susanne Langer, Kofi Agawu, Jenefer Robinson, and Roger Scruton. Much of this modern thought is rooted in theories of musical affect articulated by Plato and by others, such as Aristotle and Diogenes of Babylon, who took Plato’s work forward. The ideas which underlay such theories – ideas such as representation (μίμησις) and ethical disposition (ἦθος) – are issues of longstanding interest in Classical scholarship. But there has not yet been a monograph devoted directly to musical representation in the Hellenic tradition, despite the centrality of the subject to the subsequent philosophy of art. This dissertation fills that gap in the literature by offering an intellectual history of musical representation and expression in Greek thought from its seminal description in Plato until its fulsome rejection in the 1st century BC by Philodemus of Gadara.